2010
DOI: 10.1017/s136898001000159x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating regional differences in breast-feeding in French maternity units: a multi-level approach

Abstract: Objectives: To study how individual and regional characteristics might explain regional variations in breast-feeding rates in maternity units and to identify outlier regions with very low or high breast-feeding rates. Design: Individual characteristics (mother and infant) were collected during hospital stay. All newborns fed entirely or partly on breast milk were considered breast-fed. Regional characteristics were extracted from census data. Statistical analysis included multi-level models and estimation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
3
12
0
3
Order By: Relevance
“…That is, higher levels of education, being of immigrant status and not smoking during pregnancy increased the odds of breastfeeding initiation with the cohort infant. These findings are largely consistent with the literature suggesting the stability of these determinants over the past few decades [17,29,40]. Of interest, the effect of maternal education at the university level differed between the cohorts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…That is, higher levels of education, being of immigrant status and not smoking during pregnancy increased the odds of breastfeeding initiation with the cohort infant. These findings are largely consistent with the literature suggesting the stability of these determinants over the past few decades [17,29,40]. Of interest, the effect of maternal education at the university level differed between the cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…According to national census data, the rates of infants who were ever breastfed in France were among the lowest across European and North American countries, reported as less than 70% [8,14]. National breastfeeding initiation statistics collected in 1998, 2003, and 2010 were estimated at 52.5%, 62.6%, and 68.7% respectively [15–16], with notable differences between regions [17]. By 2011, data from the French Longitudinal Study of Children (ELFE), a population-based sample comprised of ~18, 000 families, revealed a promising rise to 70.5% of infants who were ever breastfed [18].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the proposition that reduced maternal selfconfidence and self-esteem is sometimes in the path between SPVP and EBF seems quite tenable. This hypothesis is strengthened by connecting previous findings pointing out that low confidence and feelings of worthlessness are consistent with the long-term psychological consequences of SPVP victimization (38,39) , and with other studies indicating that the psychosocial wellbeing of women during pregnancy is an important protective factor for early weaning (5,(40)(41)(42)(43)(44)(45)(46)(47) . The importance of maternal self-esteem as a mediator of the relationship between SPVP and EBF is also reasonable when comparing the gradual effects of introducing the dimensions in the multivariate model.…”
Section: Discussionsupporting
confidence: 84%
“…Though they were less likely to return to work within the child's first year, women born outside of France were more likely to combine ABF and work, regardless of other co-variates. Birthplace abroad was previously highlighted as a prominent BF determinant in developed countries [42]: community norms and dissemination across generations may account for such findings. Thus, ABF behavior of foreign women who return to work *Covariate kept in the final multivariate model, since removing it modified the OR of "Workers" by more than 10%.…”
Section: Discussionmentioning
confidence: 93%